Petrogenesis of Triassic Caojian A-type rhyolites and associated I-type granites in the southeastern Tibetan Plateau: rejuvenation of crystal mush. (2nd March 2022) - Cong, Feng; He, De-Feng; Ji, Wei-Qiang; Huang, Liang; Xiong, Bo; Zhang, Shao-Hua; Huang, Xiao-Ming
Abstract: The orogenic process and crustal growth of the Changning–Menglian Palaeo-Tethys orogenic belt in the southeastern Tibetan Plateau is not fully understood. Triassic Caojian rhyolites and granites occur extensively in this orogenic belt and represent important constraints for this issue. This study aims to examine the relationships between the Triassic Caojian rhyolites and granites and to gain a better understanding of their possible petrogenesis. The study used zircon U–Pb geochronology, trace element analyses and Sr–Nd–Hf isotope data to better understand the relationships and possible origin of the rhyolites and granites. Recent zircon U–Pb ages indicated that the Caojian rhyolites were emplaced at 227.2 Ma, whereas age estimates for Caojian granites were slightly older (233.4–236.9 Ma). The Caojian rhyolites are enriched in large-ion lithophile elements and high-field-strength elements, with elevated FeO tot /MgO and Ga/Al ratios. However, they are significantly depleted in Ba, Sr, Eu, P and Ti. These geochemical characteristics indicate that they have an A-type affinity. Furthermore, the Caojian granites comprise biotite monzogranites and granodiorites and show unfractionated composition. Mineralogically, the Caojian granites were found to contain diagnostic I-type minerals such as hornblende. Geochemical data suggest that the petrogenesis of the Triassic Caojian rhyolites is characterized by rejuvenation of crystal mush represented by the Triassic Caojian granites. The necessary thermal input was supplied by mafic magma. This magmatic evolution was likely related to lithospheric delamination and upwelling of the asthenosphere during the Mid- to Late Triassic, forming post-collisional I-type granites and A-type volcanics in the Changning–Menglian Palaeo-Tethys orogenic belt.